DIVERSITY OF MEDICAL DISCOURSES AND THEIR IMPACT UPON INDIVIDUAL’S NARRATIVES ABOUT ILLNESS IN WEST SUMATERA - Majer, Jiri (Komunitas, 2013)
AbstractThe aim of this article is to give concrete examples of how narratives influence the way person speaks about and interpret his illness. The research was conducted in West Sumatera where people are exposed to a diverse range of health discourses: western medicine, local ethno-medicine or Islamic way of treatment called ruqyah and its discourse changes the interpretation of one`s health condition. This study is part of my research, which focused on the process of creation and negotiation of a diagnosis within a multi-cultural and multi-discursive context of Indonesia. This study concludes that people in West Sumetara withdraws from several different discourses to give meaning to both their health and illness. AbstrakTujuan artikel ini adalah untuk mengilustrasikan contoh konkrit narasi, dan pengaruhnya bagi cara seseorang berbicara dan memaknai penyakit tertentu yang mereka alami. Penelitian dilakukan di Sumatera Barat, yang memiliki keragaman diskursus kesehatan: obat-obatan barat, cara pengobatan tradisional atau pengobatan secara ruqyah di dalam Islam. Penelitian ini merupakan bagian dari penelitian saya, yang difokuskan pada proses kreasi/negosiasi karena keanekaragaman budaya dan wacana kesehatan di Indonesia. Kajian ini menyimpulkan bahwa individu mengambil dari berbagai wacana kesehatan untuk memahami dan memberi makna tentang sehat dan sakit mereka.© 2013 Universitas Negeri Semarang